Many a new day [compact disc] - Rodgers, Richard, 1902-1979 (Motema Music, 2015)
Four-time Grammy-nominated jazz vocal star Karrin Allyson delivers witty, romantic and swinging takes on songs that have become part of the cultural fabric. Her multi-faceted voice shines brilliantly with accompaniment from Kenny Barron and John Patitucci.